Melatonin maintained higher contents of unsaturated fatty acid and cell membrane structure integrity in banana peel and alleviated postharvest chilling injury. (15th December 2022) - Wang, Zhiqiang; Zhang, Lin; Duan, Wenhui; Li, Wen; Wang, Qing; Li, Jiangkuo; Song, Hongmiao; Xu, Xiangbin
Highlights: Melatonin alleviated the development of chilling injury in banana fruit. Melatonin induced the unsaturated fatty acid and phospholipids accumulation. Melatonin reduced the activities of POD, CAT and AAO in banana fruit. Melatonin increased the expression of omega-3/6 fatty acid desaturase. Melatonin enhanced the desaturation activity of saturated fatty acids. Abstract: Exogenous melatonin confers the chilling tolerance of banana fruit by promoting reactive oxygen species (ROS) scavenging system and inducing the unsaturated fatty acid synthesis. The results showed that melatonin treatment increased the contents of phospholipids, promoted the ROS scavenging enzyme, and restrained the activities of lipoxygenase (LOX), and thus reduced the lipid peroxidation of banana peel. In addition, melatonin treatment increased the flavonoids and proline contents, which was conducive to antioxidant capacity. Interestingly, the enhanced antioxidant capacity is conducive to the stability of unsaturated fatty acids and reduce the enzymatic browning reaction. Moreover, melatonin treatment induced the expression of omega-3/6 fatty acid desaturase and triggered the fatty acid metabolism activity, by which maintained higher contents of unsaturated fatty acid in banana peel. Moreover, melatonin treatment stimulated the accumulation of fatty acids in banana peel, and was involved in alleviating fruit chilling injury.